Understanding and managing hazards of lithium‐ion battery systems. Issue 3 (3rd August 2022) - Snyder, Mike; Theis, Amy
Abstract: Over the last decade, the rapid development of lithium‐ion battery (LIB) technology has provided many new opportunities for both Energy Storage Systems (ESS) and Electric Vehicle (EV) markets. At the same time, fire and explosion risks associated with this type of high‐energy battery technology have become a major safety concern. Many advances have been made in understanding reactive chemistry and fire‐safety issues related to both thermal runaway and fire hazards presented by LIBs. Thermal runaway or fire can occur from battery manufacturing defects, charging system malfunctions, extreme abuse conditions that may result from a faulty operation or traffic accidents, and end‐of‐life battery handling. Failure of the battery is often accompanied by the release of toxic gas, fire, jet flames, and explosion hazards, which present unique exposures to workers and emergency response personnel. LIB fires often present complex emergency response challenges, requiring extensive amounts of water applied over several hours to cool batteries, extinguish the fire, and prevent reignition. This paper overviews the fundamental principles required to establish a basis of safety for proper storage, handling, and use of LIBs. Starting with an overview of the technology used in LIB systems, the paper will provide a review of common sources for thermal runaways and fire events and practical ways used to prevent their occurrence. While regulatory coverage for LIB storage, handling, and use is still in various stages of development, a growing body of international best practices and consensus views have emerged. Finally, to safely address thermal runaway and fire events, an overview of global best practices for emergency response activities involving LIBs is provided.